Nilai-Nilai Pendidikan Karakter dalam Tradisi Ta’dzim terhadap Kiai di Pesantren Mahasiswa An Najah Purwokerto - Fahim Yustahar (Matan : Journal of Islam and Muslim Society, 2022)
Pesantren is an Islamic educational institution that aims to prepare students to become a pious and amil religious knowledge, have noble character and always be devoted to Allah Swt One of the educational methods applied by pesantren is to cultivate the tradition of ta’dzim towards the kiai. This study aims to obtain an overview of the values of character education in the ta’dzim tradition at the An Najah Student Islamic Boarding School, Purwokerto, Banyumas Regency. To answer these questions, field research (field research) was used, while the data collection process was carried out using observation, interviews and documentation methods, while the research subjects were caregivers, administrators, students, and other related subjects. The data were analyzed using three work paths, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that: the values of character education contained in the ta’dzim tradition of kiai at the An Najah Student Islamic Boarding School, Purwokerto, Banyumas Regency, namely divine values and human values.